KATA-KATA TABU DALAM FILM BAD TEACHER KARYA LEE EISENBERG DAN GENE STUPNITSKY (SUATU ANALISIS SOSIOLINGUISTIK) - MANOPO, JESIKA REGINA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This research is motivated by finding of problems that is to classify the taboo words in the movieâ€œBad Teacherâ€. Therefore, the writer identifies taboo words that are used in the movie with the aims to classify and describe the types of taboo words by using the theory of Wardhaugh (1986). The result shows that there are seven types of taboo words, those are taboo words related to mother in law, animal, sex, death, excretion, bodily function, and religion. Based on the theory of Trudgill (1974), there were eight types of taboo words in which they related to the magic, death, left-hand, family relationship, animal, sex, excretion, and Christian religion. This research uses descriptive method and conducted in three steps : first preparation, in this case the writer watches the movie to get a good understanding. Second, data collection, the writer accesses the internet to get the movie script, then the writer reads the script and find out the conversations that contain taboo words. Third, analyzes data descriptively based on the theory of Wardhaugh. After doing identification, classification, and analysis, the conclusion is that taboo words which are used in the movie are expressing the feelings anddescribing regards intimacy within a group. Â Keywords : Taboo Words, Movie:Bad Teacher, theory:Wardhaugh, Trudgill.